A ‘giant’ Paleocene cerambycid (Coleoptera) from Menat Konservat-Lagerstätte, France - Nel, André; Kirejtshuk, Alexander; Garrouste, Romain (European Journal of Taxonomy, 2024)
Palaeosphryon menatensis gen. et sp. nov., first unambiguous representative of the longhorn beetle subfamily Prioninae from the Paleocene of Menat (France), is described and illustrated. The new fossil is placed into the tribe Prionini, showing some similarities with some species of the extant genera Osphryon (Papua New Guinea) and Titanus (Brazil, Colombia, Guianas, Ecuador, Peru), viz. in general body shape, antennomere 3 as long as first and second together but shorter than the length of fourth plus fifth, elongate elytra, and small spines on the lateral margin of the pronotum disposed in a relatively similar way as in Osphryon. Nevertheless, the exact affinities of the new fossil within the Prionini remain uncertain because of the lack of a recent phylogenetic analysis in which it could be integrated. This fossil beetle is exceptional for its very large size, with a body 70 mm long. Some other large longhorn beetles have been found in the same outcrop, and are awaiting description. The positions of the previously described Cerambycidae from Menat are also discussed. This exceptional fauna of Cerambycidae is in accordance with the current palaeoenvironmental reconstruction for the Menat Konservat-Lagerstätte, as a small maar lake surrounded by a warm and humid, probably evergreen forest.